A molecule that detects the length of DNA by using chain fluctuations. (20th May 2016) - Iwasa, Kuni H; Florescu, Ana Maria
Abstract: A class of nucleosome remodelling motors translocates the nucleosomes, to which they are attached, towards the middle of the DNA chain in the presence of ATP during in vitro experiments. This biological activity is likely based on a physical mechanism for detecting and comparing the lengths of the flanking polymer chains. Here we propose that a pivoting mode of DNA fluctuations near the surface of the nucleosome coupled with a binding reaction with a DNA binding site of the motor provides a physical basis for length detection. Since the mean frequency of the fluctuations is higher for a shorter chain than a longer one due to its lower drag coefficient, a shorter chain has a higher rate of receptor binding, which triggers the ATP-dependent activity of the remodelling motor. The dimerisation of these units allows the motor to compare the length of the flanking DNA chains, enabling the translocation of the nucleosome towards the centre of the DNA.